2019
DOI: 10.1136/bmjopen-2019-029741
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ‘universal-reporter’ outcome measure (UROM) for patient and healthcare professional completion: a mixed methods study demonstrating a novel concept for optimal questionnaire design

Abstract: ObjectivesTo describe the novel concept of, and methods for developing, a ‘universal-reporter’ outcome measure (UROM); a single questionnaire for completion by patients and/or healthcare professionals (HCPs) when views on the same subject are required.DesignA mixed methods study with three phases—phase I: identification of relevant content domains from existing clinical tools, patient questionnaires and in-depth interviews with multistakeholders; phase II: item development using a novel approach that considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The WHQ was originally developed and validated in the UK (English language) to assess post-discharge infections after abdominal surgery 22 , 23 . The WHQ was designed to be completed either by healthcare professionals or patients 24 , and, as such, has been described as a ‘universal-reporter’ outcome measure (‘UROM’) 25 . In a UK validation study, the WHQ demonstrated good reliability and high sensitivity and specificity when discriminating between SSI and no SSI in comparison with an in-person US CDC assessment 22 , 23 .…”
Section: Methodsmentioning
confidence: 99%
“…The WHQ was originally developed and validated in the UK (English language) to assess post-discharge infections after abdominal surgery 22 , 23 . The WHQ was designed to be completed either by healthcare professionals or patients 24 , and, as such, has been described as a ‘universal-reporter’ outcome measure (‘UROM’) 25 . In a UK validation study, the WHQ demonstrated good reliability and high sensitivity and specificity when discriminating between SSI and no SSI in comparison with an in-person US CDC assessment 22 , 23 .…”
Section: Methodsmentioning
confidence: 99%
“…The WHQ includes 19 items (18 items and 1 subitem) related to the construct of surgical wound healing, with 11 items (10 items and 1 conditional subitem) related to symptoms of SSI, and 8 items related to interaction with the treatment pathway for SSI. It was designed so that it could either be administered by a healthcare professional, or self-reported by patients 27 (a universal-reporter outcome measure 28 ). Two developers of the WHQ were collaborating members of the Study Management Group.…”
Section: Methodsmentioning
confidence: 99%
“…We designed a questionnaire based on a literature review. [24][25][26][27][28][29][30][31][32][33] We applied knowledge, attitudes, beliefs, and practices (KABP) theory, which holds that changes in human behavior involve 3 consecutive processes: acquiring knowledge, generating belief, and forming behavior. [34,35] Therefore, 3 consecutive elements constituted the main body of the questionnaire:…”
Section: Questionnaire Designmentioning
confidence: 99%